2019
DOI: 10.21608/auej.2019.43430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flangewidth on Shear Strength of R.C T-Beams

Abstract: This search represented tests of reinforced concrete beams were tested in laboratory for shear strength. Beams consisted of six of reinforced concrete beams without stirrups, one with Rsec and five with T-sec, with variable flange width to web width ratio. All beams were loaded under two identical point load till failure. During loading of beams deflection was measured, steel strain at mid span, steel strain at mid shear span, stains at inclined strut, and strain at upper flange. Code equations usually does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…By increasing the width ratio ρ b from 3 to 5, the ultimate load P u increased from 6% to 8% for the first group, which did not have any reinforcement in the flange. This is in line with results published in [10] where increasing the effective flange width ratio from 1 to 6 increased the shear strength by about 10 to 30%. When compared to the rectangular specimen "control", we found that P u increased by 165% to 307% due to the existence of compressed thick flanges, a result that agrees with a previous remark that the contribution of concrete compression for beams with T-section chords may be very important, as opposed to what is considered by most existing codes [9].…”
Section: Ultimate Loadsupporting
confidence: 93%
See 2 more Smart Citations
“…By increasing the width ratio ρ b from 3 to 5, the ultimate load P u increased from 6% to 8% for the first group, which did not have any reinforcement in the flange. This is in line with results published in [10] where increasing the effective flange width ratio from 1 to 6 increased the shear strength by about 10 to 30%. When compared to the rectangular specimen "control", we found that P u increased by 165% to 307% due to the existence of compressed thick flanges, a result that agrees with a previous remark that the contribution of concrete compression for beams with T-section chords may be very important, as opposed to what is considered by most existing codes [9].…”
Section: Ultimate Loadsupporting
confidence: 93%
“…The shear strength of RC T-beams without stirrups was studied in [8][9][10]. Thamrin et al [8] found that the shear strength of T-beams was affected by both the flange size and the main longitudinal reinforcement in the web.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation